Measuring the Effectiveness of Four Restoration Technologies Applied in a Degraded Alpine Swamp Meadow in the Qinghai-Tibet Plateau, China - Wei, Xiaoyan; Mao, Xufeng; Wang, Wenyin; Tao, Yaqin; Tao, Zhifa; Wu, Yi; Ling, Jiankang (Journal of Environmental Accounting and Management, 2026)
To assess the effectiveness of the four restoration techniques (one mono-technology, three combined technologies) on a degraded meadow swamp in Three-river Source Region, we developed a Biology-Environment-Service assessment framework that incorporates 12 indicators from plant, soil to ecosystem services. Two years (2018 and 2019) field monitoring and experimental data revealed that a good restoration effect achieved by the ecological restoration project. The average comprehensive restoration index (CRI)of four restoration sites are, respectively, 0.68, 0.89, 0.71 and 0.84, belonging to a level of GOOD or EXCELLENT. Restoration effect of ensemble restoration technologies is about 4.4%-30% better than that of single fencing. The vegetation restoration was about 2.8 times faster than that of soil and ecosystem services under the same restoration technology during research periods. Restoration effect presented significant difference in respond to various restoration techniques. A combination restoration measue (Fencing + water reservation + reseeding) is recommended as a potential effective restoration method for early stage of alpine wetland restoration.